2017
DOI: 10.1590/0103-8478cr20170210
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing effect of eugenol and essential oils in Pomacea canaliculata

Abstract: This study evaluated the potential relaxing and/or molluscicidal effects of eugenol and essential oils of Origanum majorana, Ocimum americanum, Hesperozygis ringens, and Piper gaudichaudianum in the gastropod Pomacea canaliculata. Compounds were tested at concentrations of 100, 250, 500, and 750µL L-1 to evaluate the relaxing effects. In the second experiment, animals were exposed to 10, 25, and 50µL L-1 of essential oils of H. ringens and P. gaudichaudianum for a period of 24h for the evaluation of molluscici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The relaxation and recovery effects of thymol on juvenile apple snails before death seemed similar to the effects reported for eugenol and essential oils of leaves from O. Majorana and O. americanum on juvenile apple snails from Brazil (Bianchini et al, 2017). Bianchini et al (2017) suggest that eugenol and the essential oil of O. americanum and O. majorana promoted muscle relaxation in P. canaliculata.…”
Section: Mode Of Actionsupporting
confidence: 75%
See 1 more Smart Citation
“…The relaxation and recovery effects of thymol on juvenile apple snails before death seemed similar to the effects reported for eugenol and essential oils of leaves from O. Majorana and O. americanum on juvenile apple snails from Brazil (Bianchini et al, 2017). Bianchini et al (2017) suggest that eugenol and the essential oil of O. americanum and O. majorana promoted muscle relaxation in P. canaliculata.…”
Section: Mode Of Actionsupporting
confidence: 75%
“…(Singh et al, 2010) explained that the eggshell of P. canaliculata is mainly composed of calcium carbonate and attached organic matter. (Bianchini et al, 2017) demonstrated that many essential oils directly damage the P. canaliculata shell.…”
Section: Mode Of Actionmentioning
confidence: 99%
“…According to Bianchini et al (2017), eugenol presents muscle relaxing activity in mollusks of the species Pomacea canaliculata. This effect may have important applications for pest control in agriculture.…”
Section: Fruitsmentioning
confidence: 99%